Kecerdasan Emosional Dan Kecemasan Mahasiswa Bimbingan Skripsi di Universitas Syiah Kuala - Fikry, Teuku Rijalul; Khairani, Maya (JURKAM: Jurnal Konseling Andi Matappa, 2017)
Undergraduate research is the final project in order to completed the undergraduate degree. It is made by a college?s student under supervision. The direction process often cause anxiety for student. Anxiety is an emotional reaction of fear and anxious, thus requires the ability to control emotions such emotional intelligence. This study aimed to see the relationship of emotional intelligence and anxiety in Syiah Kuala University?s student while getting direction of research. The study was conducted on 257 student that were selected by purposive sampling technique. The data was collected by Schutte Emotional Intelligent Scale (SEIS) from Schutte, et al (1998) and anxiey scale of Depresion Anxiety Stress Scale (DASS) that has been adapted by Damanik (2011). Data were analyzed by spearman technique with result p=0.000 (p=0.05) and correlation coefficient score -0.139. This show a negative relationship between emotional intelliegence and anxiety on Syiah Kuala University?s student while getting direction of research with 4.3% contribution (r-squared=0.043). It?s mean individual with the high level of emotional intelligence followed by the low level of anxiety, and vice versa.